Evidence for a role of viruses in the thermal sensitivity of coral photosymbionts - Levin, Rachel Ashley (ISME J, 2017)
Symbiodinium, the dinoflagellate photosymbiont of corals, is posited to become more susceptible to viral infections when heat-stressed. To investigate this hypothesis, we mined transcriptome data of a thermosensitive and a thermotolerant type C1 Symbiodinium population at ambient (27 °C) and elevated (32°C) temperatures. We uncovered hundreds of transcripts from nucleocytoplasmic large double-stranded DNA viruses (NCLDVs) and the genome of a novel positive-sense single-stranded RNA virus (+ssRNAV). In the transcriptome of the thermosensitive population only, +ssRNAV transcripts had remarkable expression levels in the top 0.03% of all transcripts at 27 °C, but at 32 °C, expression levels of +ssRNAV transcripts decreased, while expression levels of anti-viral transcripts increased. In both transcriptomes, expression of NCLDV transcripts increased at 32 °C, but thermal induction of NCLDV transcripts involved in DNA manipulation was restricted to the thermosensitive population. Our findings reveal that viruses infecting Symbiodinium are affected by heat stress and may contribute to Symbiodinium thermal sensitivity.